Czy powinniśmy wyodrębniać prawo gospodarcze? Powrót do dyskusji - Bator, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
In the paper the author recalls the debate that took place in 1993 in the pages of the journal Ruch Prawniczy, Ekonomiczny i Socjologiczny. Its editors asked the participants what business law is and whether business law should be distinguished as a branch of law and, respectively, an independent research discipline. The presented text is an attempt to show what has changed in the scientific environment of Polish jurisprudence in the less than 30 years since that debate and how these changes may affect the theses formulated in that discussion. These changes were shaped by the so-called “pragmatist turn.” Using the research assumptions of pragmatist philosophy, the author formulates a view that the idea of a branch (object) division of the system of law should be replaced by understanding “business law” as a certain attitude adopted towards the law by an acting/managing subject.
Keywords: business law; branch of law; pragmatist turn